Politics and Prejudice: How Political Discussion With Peers Is Related to Attitudes About Immigrants During Adolescence - Bohman, Andrea; Hjerm, Mikael; Eger, Maureen A. (Frontiers in Sociology, 2019)
Research on prejudice has shown that with whom we surround ourselves matters for intergroup attitudes, but these studies have paid little attention to the content of those interactions. Studies on political socialization and deliberation have focused on the content of interaction by examining the transmission of norms as well as the direct consequences of political discussion on attitudes and behavior. However, this literature has not focused on prejudice as a potential consequence. In this study, we combine these approaches to examine if political discussions with peers during adolescence matter for prejudice. We rely on five waves of a Swedish panel of adolescents, ages 13-22. Results show an association between political discussion and prejudice over time, and that this relationship increases as adolescents grow older. Results also demonstrate that the effect of political discussions depends on the level of prejudice in one’s peer network. Discussion with low prejudice friends is associated with lower levels of prejudice over time, while political discussion with high prejudice peers is not significantly related to attitudes.